2022
DOI: 10.1080/21678421.2022.2101926
|View full text |Cite
|
Sign up to set email alerts
|

Three different short-interval intracortical inhibition methods in early diagnosis of amyotrophic lateral sclerosis

Abstract: Introduction, Methods, Results, Discussion: 3170 Number of figures: 5 Number of color figures: 3 Number of tables: 1 Three different short-interval intracortical inhibition methods in early diagnosis of amyotrophic lateral sclerosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…1 Case reports with similar clinical features have been documented and diagnostic criteria for a unique clinical entity have been proposed. 2 With results from short-interval intracortical inhibition (SICI) transcranial magnetic stimulation (TMS) studies, 3 we present a case of Mills' syndrome with evidence of cortical hyperexcitability corresponding to the asymptomatic limb.…”
Section: Hyperexcitability Of the Asymptomatic Motor Cortex In A Case...mentioning
confidence: 99%
“…1 Case reports with similar clinical features have been documented and diagnostic criteria for a unique clinical entity have been proposed. 2 With results from short-interval intracortical inhibition (SICI) transcranial magnetic stimulation (TMS) studies, 3 we present a case of Mills' syndrome with evidence of cortical hyperexcitability corresponding to the asymptomatic limb.…”
Section: Hyperexcitability Of the Asymptomatic Motor Cortex In A Case...mentioning
confidence: 99%
“…Across the range of measures obtained in relation to motor cortical function, reduction of SICI appears the be the most sensitive TMS biomarker of cortical hyperexcitability, reliably differentiating ALS from mimic disorders at an early stage in the disease process [67]. Newly developed parallel threshold-tracking methods have demonstrated even greater sensitivity to distinguish mimics compared with conventional protocols [68 ▪ ]. A recent study also identified a distinct pattern of cortical excitability across cognitive phenotypes in ALS.…”
Section: Cortical Hyperexcitability As a Diagnostic Biomarkermentioning
confidence: 99%
“…Thus, T‐SICIp avoids a systematic methodological limitation of T‐SICIs that SICI values at one ISI are strongly biased by the SICI values of the preceding ISI 12 . Furthermore, in a head‐to‐head comparison of the three SICI methods in the early diagnosis of ALS, the improved methodology of T‐SICIp was more sensitive than either T‐SICIs 14 or A‐SICI 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…If caffeine does alter corticospinal excitability as measured with SICI, control for caffeine consumption would be important. in the diagnosis of amyotrophic lateral sclerosis 10–12,14,15,19,20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation